PROSPECTS OF MICRO- AND NANO-SIZED SILICON-BASED THERMOELECTRIC MATERIALS - Z.M. Sakhibova; Sotvoldieva Maftuna (Лучшие интеллектуальные исследования, 2024)
Abstract: In this article, the role of granulated semiconductors in the development of science and technology, their microstructure, thermoelectric properties, semiconductor devices made on their basis, electrophysical and thermoelectric properties of solar cells, thermocouples and integrated microcircuits, as well as the influence of atoms entering them, are analyzed and illuminated. is dedicated.